Consensus paper: Situated and embodied language acquisition - Reggin, L. D.; Gómez Franco, L. E.; Horchak, O.V.; Labrecque, D.; Lana, N.; Rio, L.; Vigliocco, G. (Journal of Cognition, 2023)
Theories of embodied cognition postulate that perceptual, sensorimotor, and affective properties of concepts support language learning and processing. In this paper, we argue that language acquisition, as well as processing, is situated in addition to being embodied. In particular, first, it is the situated nature of initial language development that affords for the developing system to become embodied. Second, the situated nature of language use changes across development and adulthood. We provide evidence from empirical studies for embodied effects of perception, action, and valence as they apply to both embodied cognition and situated cognition across developmental stages. Although the evidence is limited, we urge researchers to consider differentiating embodied cognition within situated context, in order to better understand how these separate mechanisms interact for learning to occur. This delineation also provides further clarity to the study of classroom-based applications and the role of embodied and situated cognition in the study of developmental disorders. We argue that theories of language acquisition need to address for the complex situated context of real-world learning by completing a “circular notion”: observing experimental paradigms in real-world settings and taking these observations to later refine lab-based experiments.